2010
DOI: 10.1007/s11259-010-9358-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial resistant Salmonella enterica serovars Enteritidis and Typhimurium isolates from animal and food in Southern Italy

Abstract: In the last two decades, the emergence and spread of antimicrobial-resistant pathogens, among them Salmonella, has become a serious health hazard worldwide, and specifically the high incidence of multidrug resistance has been encountered widely in many European countries. This study examines the antimicrobial susceptibility of Salmonella enterica strains Typhimurium and Enteritidis isolated in Campania and Calabria region (Southern Italy) from animal and food of animal origin. The relationship of antibiotic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…72.4% of Salmonella isolates in Thai meat products were resistant to ampicillin while 71.0% of isolates in Cambodian meat products were resistant to sulfamethoxazole [ 32 ]. Controversially, S. enterica isolated from animals and food of animal origin in Italy were highly resistant to ampicillin, chloramphenicol, streptomycin and tetracycline [ 39 ] and all Salmonella isolated from beef in Tunisia were susceptible to amoxicillin and clavulanic acid [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…72.4% of Salmonella isolates in Thai meat products were resistant to ampicillin while 71.0% of isolates in Cambodian meat products were resistant to sulfamethoxazole [ 32 ]. Controversially, S. enterica isolated from animals and food of animal origin in Italy were highly resistant to ampicillin, chloramphenicol, streptomycin and tetracycline [ 39 ] and all Salmonella isolated from beef in Tunisia were susceptible to amoxicillin and clavulanic acid [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However infection with Salmonella through direct contact with carrier animals on farms and in slaughterhouses can also occur (Fey et al, 2000;Hendriksen, Orsel, Wagenaar, Miko, & van Duijkeren, 2004). Worldwide, one of the most commonly isolated non-typhoid Salmonella serovars in pigs, pork and humans is Salmonella Typhimurium (Astorga Marquez et al, 2007;Boyen et al, 2008;Perugini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is a characteristic of our country, though generally in Europe the most isolated serotype remains S. Enteritidis (22). Confirming this, Gargiulo et al (16) found Salmonella Group B in birds of prey, Chiari et al (7) Perugini et al isolated Salmonella enterica strains Typhimurium and Enteritidis in Italy from animals and food such as bovine, ovine, swine and chicken meat, shellfish, eggs, bovine ad bubaline milk (31).…”
Section: Articlementioning
confidence: 86%